Multiplot Serial Narrative And Climate Change - Cabañas, Cynthia; Martorell, Sandra; Pérez, Héctor J. (Green Narratives, Ecology and Sustainability in Contemporary Television - Exploring Narrative Ecosystems, 2025)
This paper explores the role of multiplot serial narratives in shaping public awareness and understanding of climate change. It examines how television series utilize complex storytelling structures and high informational density to engage audiences cognitively and emotionally with environmental issues. Through case studies of fictional and non-fictional series, including Chernobyl, Years of Living Dangerously, and Extrapolations, the study analyzes the effectiveness of multiplot structures in fostering a nuanced portrayal of climate crises. The findings suggest that while serial fiction has the potential to enhance climate literacy, challenges remain in balancing narrative continuity and thematic focus. The paper advocates for the integration of sophisticated storytelling techniques to effectively communicate the multifaceted nature of climate change and inspire collective action.